Process of acquisition of family farming products for school feeding in the Municipality of Breves – PA (Research, Society and Development, 2021)
The Federal Constitution of 1988 guarantees good and adequate food. Although this guarantee is not present in the lives of many citizens, it is part of the list of social rights that the Brazilian people are entitled to by law, imposing this responsibility on the State. Public basic education in Brazil, by law, has the duty to offer a balanced menu in accordance with the recommendations of nutritionists, so that the school lunch can supply what is expected of an appropriate meal for students during their time at school. For this meal to reach the institution, there are several processes for choosing food and suppliers. Among the suppliers, we highlight the farmer coming from family farming. The law establishes this relationship between family farming and school meals, with principles and guidelines that seek to value the farmer's work together with the local culture. Its management is currently carried out by the National Education Development Fund through the National School Feeding Program Despite the legislation making the purchase of food directly from the family farmer mandatory, many city halls still neglect and impose bureaucratic barriers to hinder the farmer's access to the program. Thus, it is of paramount importance to research and analyze which requirements and criteria are used to select these farmers for the program at the municipal level in order to verify whether such requirements meet the local reality and if it does not suggest measures to cover them with more equity.